Studying the Radiation of a White Dwarf Star Falling onto a Black Hole - Marek Nikołajuk; Tomasz Karpiuk; Lorenzo Ducci; Mirosław Brewczyk (The Astrophysical Journal)
We investigate electromagnetic and gravitational radiation generated during the process of the tidal stripping of a white dwarf star circulating a black hole. We go beyond Chandrasekhar’s ideas and not only consider the white dwarf itself as a quantum object, but also describe the dynamics of the produced accretion disk in a quantum way. We model the white dwarf star as a Bose–Fermi droplet and use the quantum hydrodynamic equations to simulate the evolution of the black hole–white dwarf binary system. While going through periastron, the white dwarf loses a small fraction of its mass. The mass falling onto a black hole is a source of powerful electromagnetic and gravitational radiation. Bursts of ultraluminous radiation are flared at each periastron passage. This resembles the recurrent flaring of X-ray sources discovered recently by Irwin et al. Gravitational energy bursts occur mainly through emission at very low frequencies. The accretion disk, formed due to stripping of the white dwarf, starts at some point to contribute continuously to radiation of both electromagnetic and gravitational types.